2020
DOI: 10.1111/1471-0528.16150
|View full text |Cite
|
Sign up to set email alerts
|

Research priority setting in women’s health: a systematic review

Abstract: Background Developing a shared agenda is an important step in ensuring future research has the necessary relevance. Objective To characterise research priority setting partnerships (PSPs) relevant to women’s health. Search strategy Included studies were identified by searching MEDLINE and the James Lind Alliance (JLA) database. Selection criteria Priority setting partnerships using formal consensus methods. Data collection and analysis Descriptive narrative to describe the study characteristics, methods, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 16 publications
(84 reference statements)
0
30
0
2
Order By: Relevance
“…There is currently a research priority setting partnership developing research priorities for hypertension in pregnancy. 35 This work should be considered complementary to a wider agenda of reducing research waste across hypertension in pregnancy research. Such agendas have been proposed in areas relevant to women's health, including twin and multiple pregnancy research with research priority setting and core outcome set development as important components.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently a research priority setting partnership developing research priorities for hypertension in pregnancy. 35 This work should be considered complementary to a wider agenda of reducing research waste across hypertension in pregnancy research. Such agendas have been proposed in areas relevant to women's health, including twin and multiple pregnancy research with research priority setting and core outcome set development as important components.…”
Section: Discussionmentioning
confidence: 99%
“…Research priority setting presents an opportunity to develop a prioritized research agenda (17). A research priority setting study has recently been completed for infertility and identified research priorities related to the prevention, diagnosis, and treatment of male, female, and unexplained infertility (14).…”
Section: Discussionmentioning
confidence: 99%
“…The steering group was convened during the development of the study protocol, before the launch of the initial survey and interim prioritization survey, and before the consensus development meeting. A systematic review of registered, progressing, and completed priority setting research settings was completed to assist with the planning and delivery of the study (11).…”
Section: Methodsmentioning
confidence: 99%
“…This study has followed this guidance to ensure the research priorities were developed using a clear and transparent process using formal consensus development methods. The study design, development, and delivery was also informed by a systematic review of research priority setting studies relevant to women's health (11). With 388 respondents from 40 countries participating in the initial survey, 317 respondents from 43 countries participating in the interim prioritization survey, and 41 participants from 11 countries included in the consensus development meeting, the global participation achieved in this study should secure the generalizability of the results within an international context.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation